Bounce Forward: A School-Based Prevention Programme for Building Resilience in a Socioeconomically Disadvantaged Context - Kara, Buket; Morris, Rochelle; Brown, Alice; Wigglesworth, Pauline; Kania, Joshua; Hart, Angie; Mezes, Barbara; Cameron, Josh; Eryigit-Madzwamuse, Suna (Frontiers in Psychiatry, 2021)
Socioeconomic status is a strong predictor of normative development and wellbeing in young people. It is well-known that growing up in a socioeconomically disadvantaged context may lead to negative outcomes, both in childhood and in adulthood. Early intervention and prevention programmes are crucial for building resilience and improving health, wellbeing and equity. Bounce Forward is a school-based prevention programme implemented in Blackpool, a town in the United Kingdom facing multiple challenges. It was part of a whole town resilience approach and nascent global social movement known as the ‘Resilience Revolution’. Between 2017 and 2019, the programme was delivered in all Year 5 classes at every primary school in Blackpool (nschool = 36), reaching out to 3,134 students (ages 9 to 10; 50.4% male). The programme aimed to increase resilience in young people by building knowledge and skills about mental health and resilience through 10 sessions. In the current study, we longitudinally examined a range of protective factors, which are relevant to young people’s resilience, as well as their mental health outcomes at three time points: before they participated in Bounce Forward, at the end of the programme, and three to five months later, when they started Year 6. The current sample included 441 Year 5 students (54.2% male) from 11 primary schools in Blackpool. Nineteen teaching staff also participated in the study and provided qualitative data regarding the impact of the programme on their students. Results showed improvement in some areas of young people’s resilience after taking part in Bounce Forward. We also identified gender differences in several protective factors, indicating that boys may need further support. Teaching staff highlighted improvements in various areas; and also observed that their students have been using the strategies that they learnt from the programme. Altogether, findings suggested that young people benefitted from Bounce Forward. The programme is sustainable, offering a free to download teacher resource pack that allows schools to self-deliver it.